The Influence of AI Chatbot Use on Learning Among Elementary School Teacher Education Students at Universitas Islam Riau - Nuramadini, Agilia (Universitas Tanjungpura, 2025)
This study aims to determine the influence of AI chatbots on the learning process of Elementary School Teacher Education (PGSD) students at Universitas Islam Riau, class of 2022. The research employed a quantitative method with a survey approach. The population consisted of 345 students from the PGSD program at Universitas Islam Riau, class of 2022. A simple random sampling technique was used to select a sample of 104 students. The data collection techniques and instruments involved questionnaires for variables X and Y. To test the research hypothesis, the researcher applied a simple linear regression analysis. The results showed a significance value of 0.000 < 0.05, indicating that the increased use of AI chatbots contributes to an improvement in learning quality. A total of 83.6% of the variation in student learning can be explained by the use of AI chatbots, as indicated by the coefficient of determination (R ² = 0.836). The remaining 16.4% is influenced by other factors. Therefore, it can be concluded that there is a significant influence of AI chatbot use on the learning process of PGSD students at Universitas Islam Riau, class of 2022